Republic of Madagascar : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Nonobservance of Performance Criteria, and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Madagascar's Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Nonobservance of Performance Criteria. Madagascar's performance under the program was broadly satisfactory, taking into account the impact of the exogenous shocks and corrective actions taken by the authorities. Efforts to bring tax revenue and net foreign assets-the two indicative targets missed at end-June-back on track over the summer were successful. Progress was also made in structural reform, although with some delays.